"A Study Of Rh Positive Phenotypes I Genotypes Frequency Among Regular Blood Donors Of Different Ethnic Group In Hospital Usm, Kelantan" - Siti Nor Ashrah, Zahari (Universiti Sains Malaysia, 2006)
This study was perform in the Transfusion Medicine Unit of HUSM among 200 individuals from two major ethnic groups of Malay and Chinese regular blood donors of both sexes and different of age groups. The aims of this study was to determine the frequency of Rh positive phenotypes and genotypes among regular blood donors of Hospital University Sains Malaysia (HUSM). The frequency of Rh genotypes were determined by standard serological techniques. In this study nine phenotypes were found to occur in the Malay and Chinese populations. In the Malay population (n=IOO), there were seven phenotypes detected. The commonest phenotype in the Malay population was CCDDee ( Rl Rl) with the frequency of 62%. This is followed by CcDDEe (Rl R2) 19%, CcDdee (Rlr) 8%, CCDDEe (RJRz) 8%, ccDDEe ( R2r) 3%, CcDDEE (R2Rz) 2% respectively. The rarest phenotype in Malay population is ccDdee (Ro r) with the frequency of only 1%. The findings were different with the Chinese population where the rarest phenotype is CCDDEE (RzRz) with the frequency of 1% which was not present in the Malay population, like wise the ccDdee (Ro r) phenotype, it not present in the Chinese population. This was followed by ccDDEe (R2r) 2% , CcDdee (Rlr) 4%, CCDDEe (Rl Rz) 5%, and ccDDEE (R2R2) 9% respectively. The R2R2 phenotype was found to be present only in the Chinese population with quite high frequencies and was absent in the Malay population. The commonest phenotype in Chinese, CCDDee ( Rl Rl) with the frequency of 55% and followed by CcDDEe (RJR2) with frequency of 24% respectively. This kind of study should be on going and should be also extended to other categories of blood donors among other ethnic groups in Malaysia in view of keeping proper record of regular blood donors.